2010
DOI: 10.3109/08037051.2010.481812
|View full text |Cite
|
Sign up to set email alerts
|

Lack of regression of left ventricular hypertrophy is associated with higher incidence of revascularization in hypertension: The LIFE Study

Abstract: Higher Sokolow-Lyon voltage during antihypertensive treatment, but not UACR or the Cornell voltage-duration product, was independently associated with higher incidence of coronary as well as peripheral revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Of the modifiable risk factors, elevated BP is the strongest contributor to cardiovascular events. 2,15 The SPRINT study (Systolic Blood Pressure Intervention Trial) and meta-analysis including 44 989 participants have demonstrated additional benefits from more intensive BP lowering in populations at high risk of vascular disease. 6,7 Up until now, data on outcomes in hypertension-treated patients with PAD have been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Of the modifiable risk factors, elevated BP is the strongest contributor to cardiovascular events. 2,15 The SPRINT study (Systolic Blood Pressure Intervention Trial) and meta-analysis including 44 989 participants have demonstrated additional benefits from more intensive BP lowering in populations at high risk of vascular disease. 6,7 Up until now, data on outcomes in hypertension-treated patients with PAD have been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This process is termed cardiac remodelling and eventually leads to heart failure. Pathological cardiac hypertrophy has been recognized as an important predictor for cardiovascular morbidity and mortality as well as an independent risk factor for heart failure, myocardial infarction, arrhythmias and sudden death (Wachtell et al, 2007;Artham et al, 2009;Bombelli et al, 2009;Søraas et al, 2010).…”
Section: Types Of Cardiac Hypertrophymentioning
confidence: 99%
“…The presence of cardiac hypertrophy is usually an adverse characteristic of various cardiovascular disorders, and regression or prevention of cardiac hypertrophy has benefits in reducing the risk of CV events and sudden cardiac death in the hypertensive population (Wachtell et al, 2007;Artham et al, 2009;Bombelli et al, 2009;Søraas et al, 2010). As hypertension is commonly associated with the development of pathological left ventricle hypertrophy (LVH), most anti-hypertensive drugs can attenuate LVH, such as angiotensin converting enzyme (ACE) inhibitors and Ang II type 1 receptor (AT 1 R) blockers (ARB) (Solomon et al, 2011;Müller et al, 2012), calcium channel blockers (Devereux et al, 2001), and β-blockers (Cabrera- Bueno et al, 2007).…”
Section: Therapy For Cardiac Hypertrophymentioning
confidence: 99%